Risk factors for extraurothelial recurrence in upper tract urothelial carcinoma after radical nephroureterectomy: a retrospective study based on a Chinese population - Luo, Zhenkai; Jiao, Binbin; Yan, Yangxuanyu; Su, Caixia; Pan, Yijin; Zhao, Hang; Bo, Yuxuan; Zhang, Guan; Ding, Zhenshan (Frontiers in Oncology, 2023)
The risk factors for extraurothelial recurrence (EUR) after radical nephroureterectomy (RNU) in patients with upper tract urothelial carcinoma (UTUC) are currently inconsistent and unclear. In this study, we aimed to identify these risk factors and develop a grading system for EUR.We retrospectively analyzed 220 patients who underwent RNU for UTUC in our center from January 2009 to December 2020. Overall survival (OS) and extraurothelial recurrence free survival (EURFS) were compared using the Kaplan-Meier curve with a log-rank test. Univariate and multivariate Cox regression model were applied to identify the independent risk factors related to EUR.The median follow-up period was 42 (range: 2-143) months. Of the 220 patients, 61 patients developed EUR in our cohort, which had worse survival outcome.Multivariate Cox regression analysis showed pathologic stage, lymph node (LN) status, lymphovascular invasion (LVI), Ki-67, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) were independent risk factors for EUR. The Kaplan-Meier curves revealed a significant difference in EUR among the three risk groups.Our study suggests that pathologic stage, LN status, LVI, Ki-67, NLR, and PLR are independent risk factors for EUR in UTUC patients after RNU. The development of a grading system for EUR risk stratification may assist urologists in making clinical decisions regarding the management of UTUC.